Perhitungan Laju Infiltrasi pada Kebun Percontohan Fakultas Teknologi Pertanian Universitas Papua - Bertha Ollin Paga'; Reniana Reniana (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2021)
Water conditions for agricultural crops are very fluctuating as seen by the season, the location of water sources, and air conservation efforts. The provision of water for agricultural land can be endeavored by providing irrigation, in which the provision of irrigation water to the land must know the infiltration rate so that no run-off occurs. Infiltration is an important part in the hydrological cycle as well as in the process of diversifying rain into streams in rivers. Measurement of the infiltration rate is carried out by many methods, one of which is the direct measurement method, namely using the Double Ring Infiltrometer and the Horton method. The purpose of this study was to determine the infiltration rate that occurred in the Fateta Unipa demonstration plot. The method to be used is a descriptive analysis method with a quantitative approach. Measurement of the infiltration rate in the field was carried out at 1 (one) point with 3 (three) replications. Data processing is carried out by using 2 (two) processing techniques, namely the method of processing data directly from field measurements and data processing using the Horton Model. After that, a comparison is made between the direct measurement results and the measurement results using the Horton model. Based on the results of data processing, it was found that the infiltration rate at the study site, both with infiltration and horton models, was respectively 39.7 mm / minute and 21.7 mm / minute. The infiltration rates of the two methods were not significantly different.